Efetividade de intensidades diferentes de intervenções nutricionais associadas à prática de exercícios físicos sobre o estado nutricional e a qualidade da dieta de mulheres com excesso de peso na atenção primária à saúde - Paula Martins Horta (2013)
Introduction: Overweight and obesity present high prevalence rates in Brazil, which highlights the demand for nutritional interventions of greater effectiveness on the main risk factors. Objective: To analyze the effectiveness of different intensities of nutritional intervention associated with physical exercise practices on nutritional status and diet quality among overweight women within primary healthcare in Belo Horizonte, Minas Gerais. Materials and methods: This was a before-and-after intervention trial lasting six months conducted among overweight women at a public health promotion service called City Gym (CG) in Belo Horizonte/MG. At this service, oriented physical exercise practices and nutritional intervention are offered for free to its users. After joining the CG, the study participants were divided into two groups that were different regarding intervention intensity. The group characterized for having less intensity of intervention was named collective nutritional intervention group (CNIG) and consisted of collective nutritional intervention (CNI) activities developed routinely in CG. These included food and nutrition education open groups, lightning talks, operational groups, thematic stands, chat sessions and information boards. The group of women that integrated the higher intensity nutritional intervention, on the other hand, participated in these CNI activities but also had access to monthly individual nutritional intervention (INI). This group was called the individual and collective nutritional intervention group (ICNIG). After six months, changes in nutritional status, in terms of waist circumference (WC) and body mass index (BMI), and in diet quality were evaluated. The latter were obtained using the Brazilian Healthy Eating Index Revised (BHEI-R; PREVIDELLI et al., 2011) regarding total and components scores. The statistical analysis comprised the simple and paired Student t tests, Wilcoxon and Mann-Whitney tests at thesignificance level of 5% (p<0.05). Results: One hundred and three women composed the sample, 52 formed the ICNIG and 51, the CNIG. WC reductions were observed: in the CNIG from 98.2 cm to 96.6 cm (p=0.013) and in the ICNIG from 96.8 cm to 93.4 cm (p<0.0001). Additionally, the ICNIG presented reductions in body weight and BMI. Regarding diet quality, both groups showed increases in the BHEI-R score and in the solid fats, alcohol andadded sugars score. Moreover, the CNIG presented improvements in the total vegetables and pulses and meat, eggs and pulses scores and the ICNIG showed increases in the total fruits, whole fruits and milk and dairy scores, despite a reduction in the sodium score. Comparing the groups, ICNIG presented higher increases in the total fruits score (1.5 points vs. CNIG: 0.0 points; p=0.016) and in the whole fruits score (0.1 points vs. CNIG: 0.0 points; p=0.046). CNIG had a higher increase in the meat, eggs and pulses score (0.6 pointsvs. ICNIG: 0.0 points; p=0,027). Conclusion: Both interventions favored positive evolution of the womens nutritional status and diet quality. However, more pronounced results were seen in the ICNIG, thus highlighting the relevance of nutritional interventions of higherintensity for this public.